Determining malpractice by ink aging method - Dilek Salkim Islek; Esra Isat; Salih Cengiz (Medicine Science, 2017)
Document forgery is one of the most common crime types. One of the methods for detection of this type of crime is the determination of the age of the ink. The time difference between the suspected articles on the document can be easily detected by the determination of ink age. In our study case the family complained in a court of law with claiming that born of their down syndrome child was a negligence of the doctor. Court demanded us to determine that if notes written by the doctor in 2005 or after the family complained. Ink samples taken from two patient book of records were analysed and ink structures were determined with using High Pressure Liquid Chromatography (HPLC) and ages were determined with using dye ratio technique. [Med-Science 2017; 6(1.000): 136-8]